Web visibility of the Official Associations of Surveyors, Technical Architects and Building Engineers of Andalusia (Spain) - Gómez Cobos, Emilio; Martínez-Osorio Ibarra, Pilar (Revista General de Información y Documentación, 2015)
A measurement instrument is designed and tested to analyze the Web visibility of the Official Associations of Surveyors, Technical Architects and Building Engineers of Andalusia (Spain), which includes mechanisms to make an objective assessment. In order to that, a methodological development has been performed using qualitative parameters. These parameters are assigned a value, within a previously established range, for subsequent quantification. The results provide insights into the visibility of the web sites of these corporations. The tool as well as the methodology of usage is presented so that this procedure can be extrapolated to other institutions.
Keywords: Engineering Building; Evaluation web; Indicators; Measuring instrument; Measuring tool; Project Surveyors; Technical Architecture; Web Visibility